Ultrathin films for the transfer of antimicrobial agents to medical devices

JP7933801B2Active Publication Date: 2026-10-13DEPUY SYNTHES PROD INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023572591
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-24
Filing Date
2022-05-24
Publication Date
2026-10-13
Estimated Expiration
2042-05-24

AI Technical Summary

Benefits of technology

【0009】 本明細書において、手術部位における微生物増殖を低減させるための整形外科用インプラント又は整形外科用インプラントの構成要素が提供され、本体外側表面を画定する本体と、本体外側表面の少なくとも一部分に沿って配設された生分解性ポリマー薄膜と、生分解性ポリマー薄膜内に配設された気化可能な抗微生物剤と、を含み、以下のうちの1つ又は2つ以上が適用される:生分解性ポリマー薄膜は、約50~250μg/cm2の表面積コーティング重量を有するか、気化可能な抗微生物剤は、約5~85μg/cm2の表面積濃度を有するか、又は、抗微生物剤の表面積濃度は、外側表面の周縁から少なくとも0.5mmの有効抑制ゾーンを生成するのに十分である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933801000009
    Figure 0007933801000009
  • Figure 0007933801000010
    Figure 0007933801000010
  • Figure 0007933801000011
    Figure 0007933801000011
Patent Text Reader

Abstract

Orthopedic implants, and systems and kits containing the orthopedic implants, are provided that include a biodegradable polymeric film containing an antimicrobial agent, which creates an effective inhibition zone around the periphery of the implant's surface and does not create loss of release torque between interlocking implant components.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] (Cross-reference of related applications) This application claims the benefits of U.S. Provisional Patent Application Publication No. 63 / 192,339, filed on 24 May 2021, the entire contents of which are incorporated herein by reference.

[0002] (Field of Invention) This disclosure relates to an orthopedic implant having antibacterial properties. [Background technology]

[0003] Many individuals undergo orthopedic implants annually as a result of orthopedic trauma or joint replacement procedures. In the United States, according to the American Academy of Orthopedic Surgeons, more than 600,000 knee prostheses and more than 300,000 hip prostheses are implanted each year. More than one million patients receive metal implants annually to treat fractured bones. Implant-associated infection is one of the most serious potential complications associated with orthopedic implants, with infection rates exceeding 10% in some high-risk procedures and patient groups. Treating implant-associated infections is costly, as the procedure often requires surgical removal of the infected implant and long-term antibiotic treatment.

[0004] Implant-associated infections occur when bacteria contaminate a surgical wound site, attach to the surgical implant, and begin to proliferate. Bacteria growing on the implant surface often form a biomembrane, where they secrete a protective extracellular matrix and significantly reduce their metabolic activity. This biomembrane phenotype protects the bacteria from the patient's immune system and systemic antibiotics, making the treatment of implant-associated infections extremely difficult and expensive.

[0005] One solution to prevent implant-associated infections is to treat the surface of surgical implants to prevent bacterial growth and adhesion. Surgical implants have been developed that are coated with antibiotics or antimicrobial compounds to kill bacteria on the surgical wound site or implant surface before they can adhere to and grow on the implant. Examples include antimicrobial coated pacemaker pouches (TYRX® Absorbable Antimicrobial Envelope), orthopedic implants (ETN PROtect), surgical graft materials (XenMatrix® AB Surgical Graft), and sutures (VICRYL® Plus Antimicrobial Suture).

[0006] Methods for vaporizing an antimicrobial agent into a medical device such as a suture are disclosed, by placing the device in an inner package containing an antimicrobial agent source, covering the inner package with an outer package, and exposing the device and package to conditions of sufficient time, temperature, and pressure to vaporize the antimicrobial agent from the antimicrobial agent source to the device (e.g., U.S. Patents 7,513,093, 8,112,973, 8,133,437, 8,156,718, 8,668,867, 8,960,422, 9,044,531, 9,149,273, 9,474,524, 9,597,067, and 9,597,072). This vapor transfer process demonstrates the successful transfer of antimicrobial agents to polymer or paper materials (e.g., surgical sutures or packaging materials).

[0007] When applied to orthopedic implants, coatings containing antibiotics such as gentamicin may interfere with the ability to keep components (such as bone plates connecting bone fasteners) reliably connected to each other after implantation and degradation of the coating. For example, PLGA coatings containing particulate gentamicin can interfere with the locking function of trauma plates secured with bone fasteners, causing a significant reduction in the amount of torque required to release the fasteners from the plate. SUMMARY OF THE INVENTION PROBLEMS TO BE SOLVED BY THE INVENTION

[0008] There remains a continuing need for systems and techniques that impart antimicrobial properties to orthopedic implants and their components without interfering with the coupling function of such devices. MEANS FOR SOLVING THE PROBLEMS

[0009] Provided herein are orthopedic implants or components of orthopedic implants for reducing microbial proliferation at a surgical site, comprising a body defining an outer body surface, a biodegradable polymer thin film disposed along at least a portion of the outer body surface, and a vaporizable antimicrobial agent disposed within the biodegradable polymer thin film, wherein one or more of the following applies: the biodegradable polymer thin film has a surface area coating weight of about 50 to 250 μg / cm 2 or the vaporizable antimicrobial agent has a surface area concentration of about 5 to 85 μg / cm 2 or the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibition zone of at least 0.5 mm from the periphery of the outer surface.

[0010] Also provided herein are methods for preparing orthopedic implants or components of orthopedic implants that reduce microbial proliferation at a surgical site.

[0011] This disclosure also provides a system for reducing microbial infection at the surgical site of an orthopedic implant, a kit comprising at least one orthopedic implant body, and a plurality of bone fasteners, each reducing microbial infection at the surgical site of an orthopedic implant, and a method for reducing the loss of release torque resulting from antimicrobial treatment of an orthopedic implant system. [Brief explanation of the drawing]

[0012] [Figure 1A] This paper provides the results of an evaluation of the ability to coat the surface of stainless steel orthopedic implant components by tumbling them with polymer pellets. [Figure 1B] This paper provides the results of an evaluation of the ability to coat the surface of stainless steel orthopedic implant components by tumbling them with polymer pellets. [Figure 1C] This paper provides the results of an evaluation of the ability to coat the surface of stainless steel orthopedic implant components by tumbling them with polymer pellets. [Figure 2A] This paper provides the results of an evaluation of the ability of tumbling and dipping coatings to produce polymer coatings that can retain antimicrobial agents in order to provide a clinically effective inhibitory zone with respect to the coated components. [Figure 2B] This paper provides the results of an evaluation of the ability of tumbling and dipping coatings to produce polymer coatings that can retain antimicrobial agents in order to provide a clinically effective inhibitory zone with respect to the coated components. [Figure 2C] This paper provides the results of an evaluation of the ability of tumbling and dipping coatings to produce polymer coatings that can retain antimicrobial agents in order to provide a clinically effective inhibitory zone with respect to the coated components. [Figure 3A]The results of evaluating the release torque after use of a conventional polymer coating containing particulate gentamicin and the biodegradable polymer thin film of the present invention containing triclosan are illustrated as examples. [Figure 3B] The results of evaluating the release torque after use of a conventional polymer coating containing particulate gentamicin and the biodegradable polymer thin film of the present invention containing triclosan are illustrated as examples. [Figure 4] This document provides a flowchart for conducting research on bacterial colony formation, adhesion, and growth. [Figure 5] This example illustrates the migration of triclosan from an all-metal container to a stainless steel locking compression plate coated with an ultrathin poly(L-lactide) film at 130°C. [Figure 6] The S. aureus zone was obtained from a 130°C triclosan vapor transfer treated trauma plate having either a bare electropolished stainless steel surface or an annealed ultrathin poly(L-lactide) film. The sample was immediately placed on an agar injection plate or incubated in phosphate-buffered saline for 1, 24, or 72 hours. [Modes for carrying out the invention]

[0013] The inventive subject matter disclosed herein can be more readily understood by referring to the following modes for carrying out the invention, which are interpreted in relation to the appended embodiments forming part of this disclosure. It should be understood that the invention is not limited to the specific components, methods, or parameters described and / or illustrated herein, and that the technical terms used herein are for illustrative purposes only to illustrate specific embodiments and are not intended to limit the claimed invention.

[0014] All patents, patent applications, and publications cited or described herein are incorporated herein by reference.

[0015] When used above, and throughout this disclosure, the following terms and abbreviations should be understood to have the following meanings unless otherwise indicated.

[0016] In this disclosure, unless otherwise explicitly stated, the singular forms “a,” “an,” and “the” encompass plural references, and references to specific numerical values ​​encompass at least that specific value. For example, a reference to “polymer” is a reference to one or more such polymers and their equivalents known to those skilled in the art. Furthermore, where a particular element is indicated as “possibly” X, Y, or Z, such use is not intended in any case to exclude other options relating to that element.

[0017] When a value is expressed as an approximation using the antecedent “about,” it is understood that the particular value forms another embodiment. Generally, the use of the term “about” indicates an approximation that may vary depending on the desired characteristic sought by the disclosed subject matter of the invention and should be interpreted in the specific context in which it is used, based on its function. In some embodiments, “about X” (where X is a number) inclusively refers to ±10% of the stated value. For example, the phrase “about 8” may inclusively refer to a value between 7.2 and 8.8. This value may include “exactly 8.” Where present, all ranges are inclusive and combinable. For example, when listing the range “1 to 5,” the listed range should be interpreted as optionally including ranges such as “1 to 4,” “1 to 3,” “1 to 2,” “1 to 2 and 4 to 5,” and “1 to 3 and 5.” In addition, where a list of substitutes is explicitly provided, such a list may also include embodiments in which any of the substitutes may be excluded. For example, if a range "1-5" is given, such a description can support a situation where 1, 2, 3, 4, or 5 is excluded. Therefore, the statement "1-5" can support "1 and 3-5, but not 2" or simply "2 is not included."

[0018] As used herein, the "zone of inhibition" (ZOI) refers to the distance from the periphery of an implant where no measurable microbial colony-forming units (e.g., microbial activity) are present when the implant is placed in an in vitro environment inoculated with a known amount of colony-forming microorganisms. In certain literature, the ZOI is measured as the total cross-sectional length (e.g., diameter) of the region where no measurable microbial activity is present and which may also include the dimensions of the implant.

[0019] As used herein, “clinically effective inhibitory zone” means a ZOI measurement of at least 0.5 mm around an implant where there is no measurable bacterial growth.

[0020] When used in reference to chemical compounds such as antimicrobial agents, "vaporizable" means a compound that can evaporate when exposed to temperatures above 50°C under ambient pressure conditions.

[0021] As explained above, orthopedic implants are susceptible to microbial contamination, and previous efforts to impart antimicrobial properties have interfered with the ability to connect components (such as bone plates connecting bone fasteners) after implantation, ensuring they remain securely connected to one another. In many cases, specific tolerances exist for orthopedic implants to achieve proper interlocking (e.g., an IM nail entering the femoral marrow), and in such cases, it is unacceptable for the implant to contain a coating that prevents it from conforming to these tolerances. Oversized implant diameters due to thick coatings that later degrade will result in loosening or instability of the implant. In addition, implants configured to have spaces for tissue grafting are incompatible with thicker coatings that obstruct some or all of those spaces, thereby hindering the regeneration of natural tissue through grafting into the implant. For this reason, any strategy for imparting antimicrobial properties must be compatible with all intended uses of orthopedic implants.

[0022] The inventors have surprisingly discovered that by using an ultrathin biodegradable coating impregnated with an antimicrobial agent, orthopedic implants and their components can be given antimicrobial properties within a clinically significant inhibitory zone, while avoiding interference with the coupling function essential for the implant's ability to remain securely positioned at the surgical site, and appropriately avoiding situations where the implant becomes misfit to fit tolerances and tissue growth.

[0023] Accordingly, this specification provides an orthopedic implant or component of an orthopedic implant for reducing microbial growth at a surgical site, comprising a body defining the outer surface of the body, a biodegradable polymer thin film disposed along at least a portion of the outer surface of the body, and a vaporizable antimicrobial agent disposed within the biodegradable polymer thin film, wherein one or more of the following apply: the biodegradable polymer thin film has a concentration of approximately 50-250 μg / cm³ 2 The surface area coating weight of the vaporizable antimicrobial agent is approximately 5-85 μg / cm³. 2 The surface area concentration of the antimicrobial agent is either sufficient to create an effective inhibitory zone of at least 0.5 mm from the periphery of the outer surface.

[0024] Any orthopedic implant or component of an orthopedic implant may be used in accordance with this disclosure. An orthopedic implant is understood to be an implantable medical device that is a prosthesis used to help repair or replace damaged bone. An exemplary and non-limiting list of suitable orthopedic implants provided herein includes bone plates, intramedullary nails, bone screws, pins, spinal rods, K-wires, intervertebral disc replacements, metal compression staples (e.g., Nitinol), metal meshes used in craniofacial applications, external fixation screws or pins (e.g., Schanz screws and Steinmann pins), and joint replacement components used in hip, knee, and shoulder joint replacement procedures, such as acetabular cups, femoral stems, tibial trays, patellar prostheses, and femoral condyle components.

[0025] As described, orthopedic implants define an outer surface. In some embodiments, the outer surface may include a metal or metal alloy, polyaryletherketone (PAEK) or its copolymer, or polyalkene or its copolymer, or any combination of the above materials. Preferred metals include, for example, titanium, stainless steel, nickel, cobalt, chromium, and alloys thereof. Preferred polyalkenes are polyethylene or its copolymer. Suitable examples include high-density polyethylene (HDPE), ultra-high molecular weight polyethylene (UHMWPE), medium-density polyethylene (MDPE), ultra-low molecular weight polyethylene (ULMWPE), high molecular weight polyethylene (HMWPE), high-density cross-linked polyethylene (HDXLPE), cross-linked polyethylene (PEX or XLPE), linear low-density polyethylene (LLDPE), low-density polyethylene (LDPE), or very low-density polyethylene (VLDPE), as well as blends or copolymers thereof. Under certain high-temperature conditions, as further described below, those skilled in the art can determine which polyalkenes or copolymers thereof possess the necessary chemical properties to withstand conditions requiring temperatures above 100°C without, for example, thermal decomposition or other undesirable effects.Preferred examples of PAEK polymers include, but are not limited to, polyetheretherketone (PEEK), carbon-reinforced PEEK, polyetherketoneketone (PEKK), polyetherketone (PEK), or polyetherketoneetherketoneketone (PEKEKK), or blends or copolymers thereof.

[0026] The biodegradable polymer thin film is effectively formed integrally with and attached to the underlying orthopedic implant or its components. The surface area coating weight of the biodegradable polymer thin film is approximately 60-230 μg / cm². 2 It is possible. In some embodiments, the surface area coating weight of the biodegradable polymer thin film is about 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 210, 220, 230, 240, or 250 μg / cm². 2 That is the case.

[0027] Biodegradable polymer thin films may contain poly(α-hydroxyester) polymers. For example, a biodegradable polymer thin film may contain poly(glycolic acid) (PGA), poly(lactic acid) (PLA), poly(lactic-co-glycolic acid) (PLGA), poly(ε-caprolactone) (PCL), or any copolymer or mixture thereof. In one embodiment, a biodegradable polymer thin film may contain poly(l-lactic acid) (PLLA), poly(d-lactic acid) (PDLA), poly(d,l-lactic acid) (PDLLA), or any copolymer or mixture thereof.

[0028] In some embodiments, the vaporizable antimicrobial agent has a surface area concentration of about 5 to 85 μg / cm 2 . For example, the antimicrobial agent may have a surface area concentration of about 45 to 55 μg / cm 2 . In some embodiments, the vaporizable antimicrobial agent has a surface area concentration of about 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, or 85 μg / cm 2 .

[0029] The vaporizable antimicrobial agent may be any compound or substance that provides the ability to reduce the formation of microbial colony forming units on the surface of an orthopedic implant, preferably within the inhibitory zone surrounding the implant. In some embodiments, the vaporizable antimicrobial agent is a halogenated hydroxyl ether, an acyloxydiphenyl ether, or a combination thereof. In particular, the antimicrobial agent may be, for example, a halogenated 2-hydroxydiphenyl ether and / or a halogenated 2-acyloxydiphenyl ether, as represented by the following formula:

[0030]

Chemical Formula

[0031] In the above formula, each Hal represents the same or different halogen atom, Z represents hydrogen or an acyl group, w represents a positive natural number in the range of 1 to 5, and each of the benzene rings, which is preferably Ring A, may also contain one or more lower alkyl groups, lower alkoxy groups, allyl groups, cyano groups, amino groups, or lower alkanoyl groups that may be halogenated. Preferably, useful lower alkyl groups and lower alkoxy groups as substituents on the benzene ring are methyl group or methoxy group, respectively. Halogenated lower alkyl groups, and trifluoromethyl groups are preferred.

[0032] Furthermore, antimicrobial activity similar to that of the halogen-o-hydroxy-diphenyl ethers in the above formula can be obtained using O-acyl derivatives that undergo partial or complete hydrolysis under actual usage conditions. Ethers of acetic acid, chloroacetic acid, methyl or dimethylcarbamic acid, benzoic acid, chlorobenzoic acid, methylsulfonic acid, and chloromethylsulfonic acid are particularly preferred.

[0033] One particularly preferred antimicrobial agent within the range of the above formula is 2,4,4'-trichloro-2'-hydroxydiphenyl ether, commonly known as triclosan. Triclosan is a broad-spectrum antimicrobial agent used in a variety of products and is generally effective against a large number of organisms associated with SSI. Such microorganisms include, but are not limited to, the genera Staphylococcus, Staphylococcus epidermidis, Staphylococcus aureus, methicillin-resistant Staphylococcus epidermidis, methicillin-resistant Staphylococcus aureus, and combinations thereof.

[0034] In some embodiments, the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibition zone of about 0.5–4 mm from the periphery of the outer surface of the orthopedic implant or its components. For example, the surface area concentration of the antimicrobial agent may be sufficient to create an effective inhibition zone of about 0.5, 0.75, 1.0, 1.25, 1.5, 1.75, 2.0, 2.25, 2.5, 2.75, 3.0, 3.5, 3.75, or 4 mm from the periphery of the outer surface of the orthopedic implant or its components. In some embodiments, the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibition zone of about 1–2 mm from the periphery of the outer surface of the implant or its components. The surface area concentration of the antimicrobial agent may be sufficient to create the effective inhibition zone according to the above embodiments for up to about 6, 12, 18, 24, 36, 48, or 72 hours after implantation of the orthopedic implant or its components in a human subject.

[0035] A biodegradable polymer film may be present on part or all of the outer surface of the body of the implant or its components. In one embodiment, an orthopedic implant includes an opening configured to receive a fastener, and the surface of the opening includes a biodegradable polymer film. When a component of the orthopedic implant is a fastener, such as a threaded fastener, which includes a head that contacts the surface of the opening of the orthopedic implant when implanted at the surgical site, the biodegradable polymer film may be, for example, on the surface of the threaded portion of the fastener, the surface of the head, or both. In this manner, when the implant includes a bone plate or a bone fastener, both the surface of the bone plate and the surface of the bone fastener that contact each other when the respective components are implanted at the surgical site include a biodegradable polymer film. As more fully disclosed herein, the use of a biodegradable polymer film on such a surface of an orthopedic implant according to this disclosure does not interfere with the physical interaction of components configured to connect with one another.

[0036] Disclosed herein is a method for preparing an orthopedic implant or component of an orthopedic implant that reduces microbial growth at the surgical site, comprising: applying a biodegradable polymer thin film to the surface of the implant or component of the implant; and incorporating a vaporizable antimicrobial agent into the thin film, wherein the vaporizable antimicrobial agent is approximately 5-85 μg / cm³. 2 The biodegradable polymer thin film has a surface area concentration of approximately 50-250 μg / cm³. 2 The method involves having a surface area coating weight, or the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibitory zone of at least 0.5 mm from the periphery of the outer surface.

[0037] The application of a biodegradable polymer thin film to the surface of an implant or implant component is approximately 50-250 μg / cm³. 2The surface area coating weight according to this disclosure may be carried out by any technique capable of generating such a weight, such as the surface area coating weight. For example, the thin film is applied to the surface of the implant or implant component by immersion coating, i.e., by immersing the implant or implant component in a coating solution containing a biodegradable polymer. Other techniques may include spraying the coating solution containing a biodegradable polymer onto the surface of the implant or component. Those skilled in the art can readily identify other acceptable approaches for applying a biodegradable polymer thin film onto the surface of the implant or implant component.

[0038] Antimicrobial agents can be incorporated into the thin film by vapor transfer from an antimicrobial agent source. Vapor transfer processes and suitable sources of antimicrobial agents are known to those skilled in the art, and any effective method for achieving vapor transfer can be used.

[0039] According to this method, the properties of orthopedic implants or their components, biodegradable polymer films, vaporizable antimicrobial agents, inhibitory zones, and related features may be as described above in relation to the orthopedic implants or components of orthopedic implants of this disclosure for reducing microbial growth at the surgical site.

[0040] Also disclosed herein is a system for reducing microbial infection at an orthopedic implant surgical site, comprising an orthopedic implant body defining the outer implant surface, the orthopedic implant body having one or more openings extending from the outer surface through the implant body and configured to receive a bone fastener, and a bone fastener configured to be disposed within one or more openings for fixing the orthopedic implant body to bone, further comprising a bone fastener defining the outer fastener surface, a biodegradable polymer thin film disposed along at least a portion of the outer implant surface or the outer fastener surface, and a vaporizable antimicrobial agent disposed within the biodegradable polymer thin film, wherein the biodegradable polymer thin film has a concentration of approximately 50-250 μg / cm³ in the target area.2 It has a surface area coating weight and contains a vaporizable antimicrobial agent at a concentration of approximately 5-85 μg / cm³. 2 The surface area concentration of the antimicrobial agent is such that it is sufficient to create an effective inhibitory zone of at least 0.5 mm from the periphery of the outer implant surface, or the torque required to release the fastener from the corresponding opening of the orthopedic implant body after the use of an insertion torque suitable for implanting the orthopedic implant body in the subject is at least 90% of the torque required to release an uncoated and otherwise identical fastener from the corresponding opening of an uncoated but otherwise identical orthopedic implant body for up to 5 days after implantation of the orthopedic implant body.

[0041] According to this system, the use of a biodegradable polymer thin film having the properties disclosed herein on the surface of orthopedic implants and fasteners does not interfere with the physical interaction of such components when such components are configured to connect with each other to fix the implant within a surgical site, for example, on the bone surface of a target. A key measure of whether the coating on the implant surface interferes with such physical interaction is the implant system's ability to retain the amount of torque required to release each component from each other, for example, a fastener from the corresponding opening of the orthopedic implant body, after the use of an insertion torque suitable for implanting the orthopedic implant in the target. In some embodiments of this system, the torque required to release a fastener from the corresponding opening of the orthopedic implant body after the use of an insertion torque suitable for implanting the orthopedic implant body in the target is at least 90% of the torque required to release an uncoated, but otherwise identical, fastener from the corresponding opening of an orthopedic implant body, for up to 5 days after implantation of the orthopedic implant body in the target. For example, after using an insertion torque suitable for implanting an orthopedic implant body into a target, the torque required to release the fastener from the corresponding opening of the orthopedic implant body is approximately 91, 92, 93, 94, 95, 96, 97, 98, or 99% or more of the torque required to release an uncoated, otherwise identical, fastener from the corresponding opening of an uncoated, otherwise identical orthopedic implant body. Such release torque may be required over a period of up to 5 days after implantation of the orthopedic implant body in the target, for example, up to 6, 12, 18, 24, 36, 48, 60, 72, 84, 96, 108, or 120 hours.

[0042] According to this system, the properties of orthopedic implants or fasteners, biodegradable polymer films, vaporizable antimicrobial agents, inhibitory zones, and other related features may be as described above in relation to the orthopedic implants or components of orthopedic implants of this disclosure for reducing bacterial growth at surgical sites, and in relation to the methods of this disclosure for preparing orthopedic implants or components of orthopedic implants for reducing bacterial growth at surgical sites.

[0043] Also disclosed herein is a kit comprising at least one orthopedic implant body defining an outer implant surface, the orthopedic implant body having one or more openings extending from the outer surface through the implant body and configured to receive bone fasteners, and a plurality of bone fasteners configured to be disposed within at least one opening of the orthopedic implant body for fixing the orthopedic implant body to bone, each of the bone fasteners further defining an outer fastener surface, a biodegradable polymer film disposed along at least a portion of the outer implant surface of each orthopedic implant body, a biodegradable polymer film disposed along at least a portion of the outer fastener surface of each bone fastener, or both, and a vaporizable antimicrobial agent disposed within the biodegradable polymer film, wherein the biodegradable polymer film has a concentration of approximately 50-250 μg / cm³ 2 It has a surface area coating weight and contains a vaporizable antimicrobial agent at approximately 5-85 μg / cm³ of the target. 2The surface area concentration of the antimicrobial agent is such that it is sufficient to create an effective inhibitory zone of at least 0.5 mm from the periphery of the outer implant surface, or the torque required to release one of the fasteners from one of the corresponding openings of the orthopedic implant body after using an insertion torque suitable for implanting the orthopedic implant body is at least 90% of the torque required to release an uncoated, otherwise identical fastener from the corresponding opening of the orthopedic implant body in the subject for up to 5 days after implantation of the orthopedic implant body.

[0044] Therefore, the kit contains one or more orthopedic implant bodies comprising openings for receiving bone fixation devices, and multiple bone fixation devices for use in fixing the orthopedic implant bodies to bone. To the extent necessary, the kit may include multiple orthopedic implant bodies of the same or different types, and corresponding bone fixation devices that are individually different as needed for compatibility with the orthopedic implant bodies provided. The kit can be arranged, for example, to include all the implant components required to complete a particular implant procedure.

[0045] According to this kit, the properties of the orthopedic implant body or fastener, biodegradable polymer thin film, vaporizable antimicrobial agent, inhibitory zone, open torque characteristics, and other related features may be as described above in relation to the orthopedic implant or components of the orthopedic implant of this disclosure for reducing microbial growth at the surgical site, in relation to the method of the disclosure for preparing the orthopedic implant or components of the orthopedic implant for reducing microbial growth at the surgical site, and in relation to the system of the disclosure for reducing microbial growth at the surgical site of an orthopedic implant.

[0046] This disclosure also provides a method for reducing the loss of release torque resulting from antimicrobial treatment of an orthopedic implantation system, which includes an orthopedic implant body defining an outer implant surface, the orthopedic implant body further defining one or more openings extending from the outer implant surface through the implant body and configured to receive a bone stabilizer, the bone stabilizer being configured to be disposed within one or more openings to fix the orthopedic implant body to bone, the bone stabilizer defining an outer stabilizer surface, and the method comprises applying a biodegradable polymer thin film to one or both of the openings and the corresponding outer stabilizer surface, and incorporating a vaporizable antimicrobial agent into the thin film, wherein the biodegradable polymer thin film has a concentration of approximately 50-250 μg / cm³ 2 It has a surface area coating weight and contains a vaporizable antimicrobial agent at a concentration of approximately 5-85 μg / cm³. 2 The surface area concentration of the antimicrobial agent is such that it is sufficient to create an effective inhibitory zone of at least 0.5 mm from the periphery of the outer implant surface, or the torque required to release one of the fasteners from one of the corresponding openings of the orthopedic implant body after the use of an insertion torque suitable for implanting the orthopedic implant body in the subject is at least 90% of the torque required to release an uncoated, otherwise identical fastener from the corresponding opening of an orthopedic implant body that is uncoated, for up to 5 days after implantation of the orthopedic implant body in the subject.

[0047] According to this method, the properties of the orthopedic implant body or fastener, the biodegradable polymer thin film, the vaporizable antimicrobial agent, the inhibitory zone, the release torque characteristics, and other related features may be as described above in relation to the orthopedic implant or components of the orthopedic implant for reducing microbial growth at the surgical site, in relation to the method of the disclosure for preparing an orthopedic implant or components of an orthopedic implant for reducing microbial growth at the surgical site, in relation to the system of the disclosure for reducing microbial infection at the surgical site of an orthopedic implant, and in relation to the kit of the disclosure. [Examples]

[0048] The present invention is further defined by the following embodiments. These embodiments are given merely as examples, illustrating preferred embodiments of the invention, and should not be construed as limiting the scope of the appended claims. From the above considerations and these embodiments, those skilled in the art will be able to identify the essential features of the present invention and, without departing from its spirit and scope, make various changes and modifications to adapt the invention to various uses and conditions.

[0049] Example 1 - Conventional vapor transfer of antimicrobial agent to implant surface We attempted to vapor-transfer triclosan onto a metal orthopedic implant according to the process described in U.S. Patent No. 8,668,867 to determine whether the described process can effectively adhere triclosan to the metal surface.

[0050] 1) Titanium alloy (Ti-6Al-7Nb(TAN)), 2) 316L stainless steel, and 3) approximately 0.55 mg / cm³ 2 A series of metal pins (approximately 4 mm x 30 mm) including TAN pins with poly(D,L-lactide) (PLA) coating were tested.

[0051] Triclosan (IRGACARE MP Triclosan Lot No. 0013227542) was blended into a high-density polyethylene (HDPE) sheet at a concentration of 2.56% by weight.

[0052] The pins were co-packaged with a 0.62-0.66 gram triclosan-impregnated HDPE sheet (approximately 16 mg of triclosan), resulting in a four-layer package material suitable for EO sterilization. This package had an outer PET layer, a polyethylene layer, a foil moisture-proof layer, and an inner polyethylene heat-seal layer, with the foil layer (moisture-proof layer) positioned between the two layers. The package was EO sterilized and heat-treated at 55°C for 4 hours.

[0053] After the EO sterilization and heat treatment processes were completed, the antimicrobial activity of the pins was measured. 3.03 × 10⁻⁶ 9 CFU / mL of S. aureus was spread onto a pre-formed plate using a sterile cotton swab, and the pins were gently pressed onto the surface of the plate without penetrating the agar medium. The plate was incubated for 24 hours, and then the ZOI was measured for each pin.

[0054] The total zone was measured across the width (short axis) of the implant, and the results were as follows: Stainless steel: smallest observed zone of growth reduction (no ZOI), TAN: smallest observed zone of growth reduction (no ZOI), TAN-PLA: 12.4 mm ZOI.

[0055] By explaining the implant width (approximately 4.0 mm) and dividing it by two, the surrounding ZOI on each side of the implant was as follows: Stainless steel: not observed, TAN: not observed, TAN-PLA: 4.2 mm.

[0056] Therefore, the results showed that only polymer-coated pins (TAN-PLA) could provide clinically effective ZOI, while pins with only a metal substrate surface were unable to retain a clinically significant amount of triclosan.

[0057] Example 2 - Polymer migration to the implant surface by tumbling The tumbling of stainless steel material and polycaprolactone pellets at temperatures of 45–60°C was evaluated. Six 4mm diameter and 30mm length 316L stainless steel pins and one 4-hole trauma plate (DePuy Synthes 224.541, 80mm length × 13.5mm width × approximately 5mm thickness) were placed in a rubber octagonal tumbling chamber along with 245 grams of polycaprolactone pellets (Polysciences 26290-600, MW 80,000). The temperature was increased at 45, 50, 32, 54, and 56°C, with a tumbling period of 1.5–2 hours at each temperature. Tumbling medium (322 grams) was added, and heating was continued (56, 58, and 60°C). The appearance of the polycaprolactone, the appearance of the metal parts, and the mass of the metal parts were observed at each temperature increment.

[0058] The pin mass did not change noticeably across the heating range (Figure 1A). The change in mass was in the order of tenths of a milligram at the same resolution as the balance. However, a decreasing trend in the mass of the trauma plate was observed (Figure 1A). The migration of polycaprolactone could not be measured by the mass balance. However, the air-water contact angles of the pin and tumbling medium changed significantly, indicating surface modification by polycaprolactone. Microscopy demonstrated evidence of PCL migration to the surfaces of the pin (Figure 1B) and trauma plate (Figure 1C), but no PCL adhesion to the locking threads was observed (Figure 1C). This has the advantage of avoiding polymer contamination of the locking mechanism of the trauma plate.

[0059] Example 3 - Comparison between PCL tumbling, ultrathin immersion coating, and conventional polymer coatings for orthopedic implants. Samples were prepared to evaluate the minimum polymer coating that could sustain antimicrobial activity. The sample was a 54 mm × 12.5 mm 316 L plate, which was a rectangular representation of a trauma plate suitable for suppression zone studies, known as a "flat plate." Two specific processes were used: manual immersion coating in a 4.5% wt / wt polylactide-ethyl acetate solution, and tumbling in polycaprolactone pellets (245 g Polysciences 26290-500, MW 80,000) and tumbling medium (322 g) at 56°C for 16 hours. The manual immersion coating was 53 μg / cm³. 2 This resulted in an average coating weight. Polycaprolactone tumbling did not produce an increase in sample mass; rather, the tumbling process removed mass from the 316L sample (28 mg from 15.7 g in a 316L plate). However, the coating of the sample with polycaprolactone was confirmed by microscopic observation and an increase in the air-water contact angle (Figure 2A).

[0060] Triclosan vapor transfer from PE-triclosan sheet test samples was performed by placing a 0.65 ± 0.02 gram triclosan-containing PE sheet together with the material to be processed in a foil-sterilized pouch. The pouch was heat-sealed, and the triclosan transfer was completed at 55°C for approximately 4 hours.

[0061] The following samples were treated with triclosan in the same batch. 316L stainless steel pin, diameter 4mm x length 30mm. 316L flat plate, 53 μg / cm³ 2 Polylactide coated 316L plate, From Example #2, 316L pins tumbled in PCL at 60°C, 316L flat plate tumbled at 56℃ via PCL, 19mm PEEK disc, Rapidsorb 85:15 PLGA plate (Synthes PN 851.421.01S), Porous polyethylene (Synthes PN 08.510.130S cut into 13mm x 50mm pieces).

[0062] Three 0.59 mg / cm³ samples from Example 1 2 This included polylactide-coated pins. For these samples, triclosan transfer was performed during both EO sterilization and 4 hours of oven treatment at 55°C.

[0063] The antimicrobial activity of triclosan-transferred samples was evaluated by inhibitory zone analysis performed after a phosphate-buffered incubation period (Figure 2C). 8 A culture of S. aureus ATCC 25923 at CFU / mL was spread onto a pre-formed plate using a sterile cotton swab, and the sample was gently pressed onto the surface of the plate. The sample was either removed from the pouch and placed directly onto the ZOI, or incubated in 12 mL of PBS for 15 minutes or 24 hours. Samples incubated in PBS were further rinsed with 12 mL of PBS before being placed on the ZOI dish. Care was taken to place the sample on the plate with the ZOI spread so that the opposite side of the PE strip faced the bacteria. This represents the worst-case scenario regarding triclosan migration from the PE strip in the pouch. After 24 hours of bacterial growth, the zone width and sample width were measured. The suppression zone was measured as the margin from the edge of the implant, calculated as (zone width - sample width) / 2.

[0064] Table 1 illustrates the measured inhibition zones around metal pins and plates, as well as exemplary polymer medical device materials. “Shadow” refers to the smallest observed area of ​​growth reduction (no ZOI). “Local” means that the zone was observed only in a few areas adjacent to the sample; i.e., a consistent inhibition zone was not observed, but some activity was present.

[0065] [Table 1]

[0066] Solid polymer samples consistently produced suppression zones upon immediate placement on a plate spread with S. aureus, or when placement occurred 15 minutes after incubation in PBS. Zones or localized activity were present after 24 hours of incubation in PBS with solid polymer samples. Zones were not observed adjacent to stainless steel pins or plates; however, ultrathin coatings improved zone durability to incubation and rinsing in PBS. The PCL tumbling process immediately produced suppression zones, but none withstood PBS rinsing. (Ultrathin 0.53 μg / cm²) 2 The polylactide coating produced a zone that withstood a 15-minute incubation, but after a 24-hour incubation, only localized activity remained. (0.59 mg / cm³ on titanium alloy pin) 2 A thicker coating of polylactide produced a robust zone that withstood 24 hours of pre-elution. The minimum coating weight to produce an inhibitory zone after 24 hours of pre-incubation in PBS was 53–590 μg / cm³ for triclosan transfer performed at 55°C for 4 hours from 2.56% triclosan compounded on polyethylene strips. 2 That is the case.

[0067] Example 4 - Fabrication and evaluation of the suppression zone Polylactide immersion coating solutions were prepared using 5% polylactide (Evonik Resomer 203S) in ethyl acetate and 8% polylactide in ethyl acetate. These solutions were used to immerse and coat 7-well 3.5 LCP 316L trauma plates (DPS PN223.571, 98 mm long × 11 mm wide). The plates were fixed horizontally in a stainless steel mesh tray, manually immersed in each solution, and then removed to coat the plates with the solution. The plates were weighed before coating and after overnight drying, and measured at 22.72 cm². 2 The coating mass per unit area was calculated. A 5% polylactide solution in ethyl acetate yielded a coating mass of 102 ± 5 μg / cm². 2The coating weight produced was 229±14 μg / cm³ for the 8% solution. 2 The coating weight was generated. Coating in a low-viscosity polymer solution has the advantage of coating many different part sizes or shapes by a single method.

[0068] Trauma plates were co-packaged in a foil pouch with a 0.67 ± 0.02 gram polyethylene sheet containing 2.56% triclosan. Triclosan vapor transfer was performed in a preheated 55°C oven for 4 hours and 31 minutes. The suppression zone of the cooled samples was evaluated either directly from the package or after pre-elution in PBS for 15 or 24 hours. Suppression zone analysis was performed using the pour plate method as described below. • In 20 mL of TSB prepared in the laboratory, 10 9 The bacterial inoculum of Staphylococcus aureus is prepared by incubating it overnight in a shaker at 37°C at a concentration of CFU / mL. Obtain the OD600 reading of the diluted stock of the culture overnight, and determine the stock concentration by absorbance method. • Using 0.3% TSB, reduce the bacterial concentration from the stock concentration to 10, ensuring that the colony clumps are broken up by forcefully aspirating with a serum pipette. 5 Adjust to CFU / mL. • Plate the following dilutions in sets of three onto a TSA-L plate to determine the initial stock concentration of cells: 10 2 CFU / mL. Prepare the TSA (autoclave 20g of triptych soy agar in 500mL of ultrapure water at 121°C for 30 minutes), and cool the agar in a 45°C water bath. Once the agar reaches 45°C, remove the sterile petri dish. Add the inoculant (1.00E+05CFU / mL) to the center of the petri dish, then slowly pour in 15mL of TSA. Close the lid and swirl the petri dish to mix the inoculant with the agar. Avoid creating air bubbles. • Place the test sample in the center of the petri dish using sterile forceps. To allow the agar plate to gel completely, place the plate on a calm, undulating surface for approximately 10 minutes. Incubate the plate at 37°C for 24 hours. • Measure the suppression zone using image analysis.

[0069] As shown in Table 2 below, the resulting zones were 102 and 229 μg / cm³. 2 This demonstrates that a polylactide (Resomer 203S) coating allows triclosan migration at 55°C for 4.5 hours, creating an inhibition zone that withstands for at least 24 hours.

[0070] [Table 2]

[0071] Example 5 - Evaluation of the release torque of polylactide-coated trauma plates against 40% gentamicin sulfate in poly(lactide-co-glycolide)-coated plates. The locked trauma plating structure must remain locked after implantation. Approximately 3.5 mg / cm 2 A poly(lactide-co-glycolide) containing 40% particulate gentamicin sulfate coated onto a trauma plate with a coating weight of 102 μg / cm³, containing vapor-transfer triclosan prepared in Example #04. 2 and 229 μg / cm³ 2Two ultrathin polylactide coatings were compared. Locking screw heads were inserted into the plates using a calibrated torque sensor with an accuracy of 0.01 Nm. In the initial study, a target insertion torque of 2.50 Nm was used for PLGA-gentamicin plates. In the control study, a target insertion torque of 1.50 Nm was used for polylactide-triclosan plates. Each study had its own uncoated plate control group. PLGA-gentamicin plates were coated by vertical immersion coating, and results for coated proximal and coated distal holes are presented separately. Coating weight was greater for coated distal holes, indicating that they held more suspension during the coating process. Release torque was measured at 37°C for 5 days in pH 11 buffer, either on the same day or after hydration and polymer coating degradation. Release torque is presented in tables, and the % difference from release torque relative to insertion for each study group is provided in Tables 3 and 4 below.

[0072] [Table 3]

[0073] [Table 4]

[0074] As shown in Figures 3A and 3B, the conventional antimicrobial coating of PLGA contains approximately 3.5 mg / cm³ 2 Particulate gentamicin interfered with the locking function of the trauma plate, causing a significant reduction in release torque both after drying and after 5 days of incubation in pH 11 buffer. (102 or 229 μg / cm³) 2 The polylactide coating did not interfere with the locking function of the trauma plate. A 9-10% reduction in removal torque was observed during dry removal, and surprisingly, the removal torque increased after incubation in pH 11 buffer for 5 days.

[0075] Example 6 - Benchmarking Adhesion and Growth 90 μg / cm³ with triclosan vapor transfer 2 The antimicrobial colony-forming performance of polylactide-coated titanium alloy (titanium aluminum niobium) pins (4 mm in diameter x 30 mm in length) was compared with that of untreated TAN pins. Six coated TAN pins were placed in foil pouches containing 0.62–0.72 grams of polyethylene with 2.56% triclosan. These were placed in a preheated oven at 55°C for 4 hours and 5 minutes to allow the triclosan to vapor-transfer from the polyethylene to the polylactide-TAN pins. Studies of bacterial colony formation and growth were conducted using S. aureus ATCC 25923, as depicted in the flowchart shown in Figure 4. To reflect the complexity of human interstitial fluid, fetal bovine serum was used as a component of the bacterial broth, and levels of 0%, 2%, and 20% were evaluated.

[0076] Table 5 below provides the evaluation results. Pins coated with PLA-triclosan demonstrated antimicrobial activity in reducing colony formation at 24 hours, despite showing no effect on bacterial adhesion to the pins at 1 hour. The antimicrobial effect was greater than 4-log under liquid culture conditions, while the effect on soft agar ranged from 1.4-log reduction in the absence of serum to 1.9-log with 2% serum and 2.4-log with 20% serum. While not limited to any specific theory, the effectiveness of triclosan in soft agar may have increased with serum content due to the increased ability to solubilize triclosan and produce higher tissue concentrations of the compound. Triclosan vapor transfer at 55°C for 4 hours was 90 μg / cm³. 2 When performed on TAN pins coated with polylactide, antimicrobial efficacy was demonstrated.

[0077] [Table 5]

[0078] Example 7 - High heat transfer and ultrathin film Further experiments have determined that triclosan transfer performed in all-metal containers increases the amount of triclosan transferred to metal implants, especially when the container is made of metal or other triclosan-non-absorbent material. Using this approach, it is possible to simultaneously heat-sterilize the product and impart antimicrobial properties to the target device. As demonstrated in this example, combining non-absorbent packaging with a preferred absorbent coating on a metal device is particularly advantageous.

[0079] To withstand the heating required for dry heat sterilization and the simultaneous triclosan vapor transfer, the polymer coating must not melt or stick during the process, and therefore remain in its container. Poly(L-lactide), or preferably poly(D-lactide) stereocomplexed with poly(L-lactide), are candidates that remain crystalline at the relevant heat sterilization temperature. In this example, poly(L-lactide) (Lactel B6002-2 IV:0.90-1.20) was coated onto a 7-well 3.5 LCP 316L trauma plate (DPS PN223.571, 98 mm long × 11 mm wide) from a 2.5% solution in chloroform at 4, 12, and 20 mm / sec. Seven sample plates were coated at different rates and contained three samples for triclosan quantification and one sample each for ZOI by PBS incubation or pour plate deposition without pre-elution at 1 hour, 24 hours, or 72 hours. After immersion coating and air drying, the traumatized plates were annealed at 130°C to maximize the stability of the poly(L-lactide) crystalline region.

[0080] Triclosan migration was achieved by depositing 1.64 ± 0.23 mg of triclosan into each aluminum tube container by solvent casting from ethyl acetate. Coated or uncoated target trauma plates were inserted, the ends of the aluminum tubes were closed by crimping with pliers and a vise, and then the triclosan migration was completed at 130°C for 4 hours. The samples were removed, and the triclosan was quantified by UV absorbance as follows. 1.10 mg of triclosan was weighed into a 10 ml volumetric flask (amber colored). 2. Next, 10 mL of solvent was added and the powder was dissolved by vortex mixing. This was designated as the first stock concentration (1000 ppm). 3. Using a stock concentration of 1000 ppm triclosan, subsequent dilutions were performed with the following solvents:

[0081] [Table 6] 4. Next, 1 mL of each standard sample was transferred to a plastic cuvette, and the absorbance of each sample was read using 280 nm UV light. 5. Next, a standard curve for triclosan was created by plotting absorbance at 280 nm against triclosan concentration.

[0082] Sample preparation 1. Plates treated with triclosan were placed in a sterile 15 mL centrifuge tube. 2.13 mL of acetonitrile was added to each tube. The tubes were shaken at 250 rpm for the required time. 3. The pin was then moved to a separate sterile tube. The sample solution was stored at 4°C until analysis. 4. For analysis, a 15 ml centrifuge tube containing the sample was briefly vortexed. 5. Next, 1 mL of each sample was analyzed at a wavelength of 280 nm using a UV Nanodrop instrument, and the concentration of each sample was determined from the prepared standard curve. Samples that showed very high initial absorbance were diluted with acetonitrile.

[0083] Figure 5 illustrates the migration of triclosan to a stainless steel locking compression plate coated with an ultrathin poly(L-lactide) film in an all-metal container at 130°C. The degree of migration increased 4.7 times compared to the base metal plate with the thinnest coating, and the amount of deposited triclosan was relatively insensitive to the amount of coating weight.

[0084] Table 6 below provides the poly(L-lactide) coating weight, the average triclosan transferred, and the triclosan ratio for a base metal plate with dry heat sterilization and simultaneous steam transfer.

[0085] [Table 7]

[0086] The trauma plate was treated with 77, 131, and 222 μg / cm³. 2 The preparation was carried out using a base metal surface or poly(L-lactide) film having a coating weight of [amount]. The triclosan dose on the trauma plate ranged from 0.24 mg without polymer to 77 μg / cm³ with polymer. 2 Polymer, 4.7 times, 131 μg / cm³ 2 , 5.2 times, and 222 μg / cm³ 2 The amount increased 5.6 times (Figure 5). When the amount of triclosan on the trauma plate is expressed as a percentage of the initial triclosan in each container, the ultrathin polymer coating increased the migration efficiency from 12% of the untreated plate to 77 μg / cm³, respectively. 2 Regarding the coated plates, 76% and 131 μg / cm³ were observed. 2 and 222 μg / cm³ 2 The ultrathin polymer coatings were increased to 86% and 84%. Due to the high migration efficiency, the amount of triclosan deposited on the trauma plate was relatively insensitive to the amount of polymer on the trauma plate. This further reinforces the low manufacturing costs associated with the immersion coating process, as differences in the average coating weight from plate to plate do not result in significant differences in the amount of triclosan transferred to the plate during dry heat sterilization and simultaneous steam transfer. Uncoated trauma plates demonstrated an inhibition zone that withstood 24 hours of pre-elution in PBS, while all three ultrathin polymer-coated plates demonstrated an inhibition zone after 72 hours of pre-elution (Figure 6).

[0087] [Implementation Method] (1) An orthopedic implant or component of an orthopedic implant for reducing microbial growth at the surgical site, The main body defines the outer surface of the main body, A biodegradable polymer thin film is disposed along at least a portion of the outer surface of the main body, The biodegradable polymer thin film contains a vaporizable antimicrobial agent, The biodegradable polymer thin film contains approximately 50-250 μg / cm³ 2 It has a surface area coating weight, The vaporizable antimicrobial agent is present in a concentration of approximately 5-85 μg / cm³. 2 It has a surface area concentration, or An orthopedic implant or component of an orthopedic implant, wherein the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibitory zone of at least 0.5 mm from the periphery of the outer surface. (2) The surface area coating weight of the biodegradable polymer thin film is approximately 60 to 230 μg / cm² relative to the surface area of ​​the main body. 2 An orthopedic implant or component according to Embodiment 1. (3) The orthopedic implant or component according to Embodiment 1 or 2, wherein the biodegradable polymer thin film comprises a poly(α-hydroxyester) polymer. (4) The orthopedic implant or component according to Embodiment 3, wherein the biodegradable polymer thin film comprises poly(glycolic acid) (PGA), poly(lactic acid) (PLA), poly(lactic acid-co-glycolic acid) (PLGA), poly(ε-caprolactone) (PCL), or any copolymer or mixture thereof. (5) The orthopedic implant or component according to Embodiment 3, wherein the biodegradable polymer thin film comprises poly(l-lactic acid) (PLLA), poly(d-lactic acid) (PDLA), poly(d,l-lactic acid) (PDLLA), or any copolymer or mixture thereof.

[0088] (6) The antimicrobial agent is approximately 45-55 μg / cm³ 2An orthopedic implant or component according to Embodiment 1, having a surface area concentration. (7) The orthopedic implant or component according to Embodiment 1, wherein the vaporizable antimicrobial agent comprises a halogenated hydroxyl ether, an acyloxydiphenyl ether, or a combination thereof. (8) The orthopedic implant or component according to Embodiment 1, wherein the vaporizable antimicrobial agent comprises 2,4,4'-trichloro-2'-hydroxydiphenyl ether (triclosan). (9) The orthopedic implant or component according to Embodiment 1, wherein the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibitory zone of about 0.5 to 4 mm from the periphery of the outer surface. (10) The orthopedic implant or component according to Embodiment 1, wherein the surface area concentration of the antimicrobial agent is sufficient to create an effective inhibitory zone of about 1 to 2 mm from the periphery of the outer surface.

[0089] (11) The orthopedic implant or component according to Embodiment 1, wherein the surface area concentration of the antimicrobial agent is sufficient to generate the effective inhibitory zone for up to approximately 6, 12, 18, 24, 36, 48, or 72 hours after implantation of the orthopedic implant or component into a human subject. (12) The orthopedic implant or component according to Embodiment 1, wherein the biodegradable polymer thin film is present on each surface of the main body. (13) The orthopedic implant or component according to Embodiment 1, wherein the main body comprises metal, polymer, or both. (14) The orthopedic implant or component according to Embodiment 1, wherein the outer surface of the main body comprises metal, polymer, or both. (15) The orthopedic implant or component according to Embodiment 1, wherein the outer surface of the main body includes polyaryletherketone (PAEK), polyalkene, metal or metal alloy, or a combination thereof.

[0090] (16) The orthopedic implant or component according to Embodiment 1, wherein the outer surface of the main body includes metal or a metal alloy. (17) The orthopedic implant or component according to Embodiment 16, wherein the metal is titanium, stainless steel, or an alloy containing titanium or steel. (18) The orthopedic implant or component according to Embodiment 1, wherein the outer surface of the main body contains PAEK, and the PAEK is polyetheretherketone (PEEK) or a copolymer thereof. (19) The orthopedic implant or component according to Embodiment 1, wherein the outer surface of the main body contains a polyalkene, and the polyalkene is polyethylene or a copolymer thereof. (20) A method for preparing an orthopedic implant or a component of an orthopedic implant that reduces microbial growth at the surgical site, Applying a biodegradable polymer thin film to the surface of the implant or its components, This includes incorporating a vaporizable antimicrobial agent into the thin film, The vaporizable antimicrobial agent is present in a concentration of approximately 5-85 μg / cm³. 2 It has a surface area concentration, or A method wherein the surface area concentration of the antimicrobial agent is sufficient to generate an effective inhibitory zone of at least 0.5 mm from the periphery of the outer surface.

[0091] (21) The biodegradable polymer thin film contains approximately 50-250 μg / cm³ 2 The method according to embodiment 20, having a surface area coating weight. (22) The method according to Embodiment 20 or 21, wherein the thin film is applied to the surface of the implant or implant component by immersing the implant or implant component in a coating solution containing the biodegradable polymer. (23) The method according to Embodiment 20, wherein the antimicrobial agent is incorporated into the thin film by vapor transfer from the source of the antimicrobial agent. (24) A system for reducing microbial infection at the surgical site of an orthopedic implant, An orthopedic implant body defining an outer implant surface, further defining one or more openings extending from the outer surface through the implant body and configured to receive a bone fixation device, A bone fastener configured to be disposed within one or more openings for fixing the orthopedic implant body to bone, comprising a bone fastener defining the outer fastener surface, A biodegradable polymer thin film disposed along at least a portion of the outer implant surface or the outer fastener surface, The biodegradable polymer thin film contains a vaporizable antimicrobial agent, The biodegradable polymer thin film contains approximately 50-250 μg / cm³ 2 It has a surface area coating weight, The vaporizable antimicrobial agent is present in a concentration of approximately 5-85 μg / cm³. 2 Does it have a surface area concentration? Is the surface area concentration of the antimicrobial agent sufficient to create an effective inhibitory zone of at least 0.5 mm from the periphery of the outer implant surface? Or, A system in which, after using an insertion torque suitable for implanting the orthopedic implant body in the subject, the torque required to release the fastener from the corresponding opening of the orthopedic implant body is at least 90% of the torque required to release an uncoated, otherwise identical, fastener from the corresponding opening of an uncoated, otherwise identical orthopedic implant body for up to 5 days after implantation of the orthopedic implant body in the subject. (25) It is a kit, An orthopedic implant body comprising at least one orthopedic implant body defining an outer implant surface, further defining one or more openings extending from the outer surface through the implant body and configured to receive a bone fixation device, A plurality of bone fasteners configured to be disposed within at least one opening of the orthopedic implant body for fixing the orthopedic implant body to bone, wherein each of the bone fasteners comprises a plurality of bone fasteners each defining an outer fastener surface, A biodegradable polymer thin film, which is disposed along at least a portion of the outer implant surface of each of the orthopedic implant bodies, or along at least a portion of the outer fastener surface of each of the bone fasteners, or both; The biodegradable polymer thin film contains a vaporizable antimicrobial agent, The biodegradable polymer thin film contains approximately 50-250 μg / cm³ 2 It has a surface area coating weight, The vaporizable antimicrobial agent is present in a concentration of approximately 5-85 μg / cm³. 2 Does it have a surface area concentration? The surface area concentration of the antimicrobial agent is sufficient to create an effective inhibitory zone of at least 0.5 mm from the periphery of the outer implant surface, or A kit wherein, after using an insertion torque suitable for implanting the orthopedic implant body in the subject, the torque required to release one of the fasteners from one of the corresponding openings of the orthopedic implant body is at least 90% of the torque required to release an uncoated, otherwise identical, fastener from a corresponding opening of an uncoated, otherwise identical orthopedic implant body, for up to 5 days after implantation of the orthopedic implant body in the subject.

[0092] (26) A method for reducing the loss of release torque resulting from antimicrobial treatment of an orthopedic implant system, wherein the orthopedic implant system is An orthopedic implant body defining an external implant surface, further defining one or more openings extending from the external implant surface through the implant body and configured to receive a bone fixation device, A bone fastener configured to be disposed within one or more openings for fixing the orthopedic implant body to bone, comprising a bone fastener defining the outer surface of the fastener, The method described above is Applying a biodegradable polymer thin film to one or both of the opening and the corresponding outer fastener surface, This includes incorporating a vaporizable antimicrobial agent into the thin film, The biodegradable polymer thin film contains approximately 50-250 μg / cm³ 2 It has a surface area coating weight, The vaporizable antimicrobial agent is present in a concentration of approximately 5-85 μg / cm³. 2 Does it have a surface area concentration? The surface area concentration of the antimicrobial agent is sufficient to create an effective inhibitory zone of at least 0.5 mm from the periphery of the outer implant surface, or A method wherein, after using an insertion torque suitable for implanting the orthopedic implant body in a subject, the torque required to release one of the fasteners from a corresponding opening of the orthopedic implant body is at least 90% of the torque required to release an uncoated, otherwise identical fastener from a corresponding opening of an uncoated, otherwise identical orthopedic implant body in a subject for up to five days after implantation of the orthopedic implant body in the subject.

Claims

1. An orthopedic implant or orthopedic implant component for reducing microbial growth at the surgical site, A body comprising an outer surface and one or more openings, wherein the one or more openings extend from the outer surface through the body and are configured to accommodate bone fasteners inside for fixing the body to a bone, A biodegradable polymer thin film disposed along at least one or more of the openings, The biodegradable polymer thin film contains a vaporizable antimicrobial agent, The biodegradable polymer thin film is 50 to 250 μg / cm³ 2 It has a surface area coating weight, The vaporizable antimicrobial agent is present in a concentration of 5 to 85 μg / cm³. 2 An orthopedic implant or orthopedic implant component having a surface area concentration.

2. The surface area coating weight of the biodegradable polymer thin film is 60 to 230 μg / cm² relative to the area of ​​the outer surface of the main body. 2 The orthopedic implant or orthopedic implant component according to claim 1.

3. The biodegradable polymer thin film comprises a poly(α-hydroxyester) polymer, and optionally, the biodegradable polymer thin film is (a) Poly(glycolic acid) (PGA), poly(lactic acid) (PLA), poly(lactic acid-co-glycolic acid) (PLGA), poly(ε-caprolactone) (PCL), or any copolymer or mixture thereof, (b) The orthopedic implant or orthopedic implant component according to claim 1, comprising poly(l-lactic acid) (PLLA), poly(d-lactic acid) (PDLA), poly(d,l-lactic acid) (PDLLA), or any copolymer or mixture thereof.

4. The vaporizable antimicrobial agent is present in a concentration of 45-55 μg / cm³. 2 An orthopedic implant or orthopedic implant component according to claim 1, having a surface area concentration.

5. The vaporizable antimicrobial agent is (a) Halide hydroxyl ethers, acyloxydiphenyl ethers, or combinations thereof, and / or (b) The orthopedic implant or orthopedic implant component according to claim 1, comprising 2,4,4'-trichloro-2'-hydroxydiphenyl ether (triclosan).

6. The orthopedic implant or orthopedic implant component according to claim 1, wherein the biodegradable polymer thin film is present on each surface of the main body.

7. The orthopedic implant or orthopedic implant component according to claim 1, wherein the main body comprises metal, polymer, or both.

8. The outer surface of the main body is (a) metals, polymers, or both, (b) Polyaryl ether ketones (PAEKs), polyalkenes, metals or metal alloys, or combinations thereof (c) A metal or metal alloy in which the metal is optionally titanium, stainless steel, or an alloy containing titanium or steel, (d) PAEK, wherein the PAEK is polyetheretherketone (PEEK) or a copolymer thereof, and / or (e) The orthopedic implant or orthopedic implant component according to claim 1, comprising a polyalkene, wherein the polyalkene is polyethylene or a copolymer thereof.

9. A method for preparing an orthopedic implant or orthopedic implant component that reduces microbial growth at the surgical site, The orthopedic implant or orthopedic implant component includes a main body, The main body defines the outer surface of the main body and one or more openings extending from the outer surface of the main body through the main body, The one or more openings are configured to accommodate bone fasteners inside in order to fix the main body to the bone, and the method is Applying a biodegradable polymer thin film along at least one or more of the aforementioned openings, This includes incorporating a vaporizable antimicrobial agent into the biodegradable polymer thin film, The biodegradable polymer thin film is 50 to 250 μg / cm³ 2 It has a surface area coating weight, The vaporizable antimicrobial agent is present in a concentration of 5 to 85 μg / cm³. 2 A method having a surface area concentration.

10. The method according to claim 9, wherein the biodegradable polymer thin film is applied to the outer surface of the main body of the orthopedic implant or orthopedic implant component by immersing the orthopedic implant or orthopedic implant component in a coating solution containing the biodegradable polymer.

11. The method according to claim 9, wherein the vaporizable antimicrobial agent is incorporated into the biodegradable polymer thin film by vapor transfer from a source of the vaporizable antimicrobial agent.

12. A system for reducing microbial infection at the surgical site of orthopedic implants, An orthopedic implant body defining the outer surface of an implant, further defining one or more openings extending from the outer surface of the implant through the orthopedic implant body and configured to receive a bone fastening device, A bone fastener configured to be disposed within one or more openings for fixing the orthopedic implant body to bone, comprising a bone fastener defining the outer surface of the fastener, At least one or more of the openings, and one or both of the corresponding outer fastener surfaces, a biodegradable polymer thin film, The biodegradable polymer thin film contains a vaporizable antimicrobial agent, The biodegradable polymer thin film is 50 to 250 μg / cm³ 2 It has a surface area coating weight, The vaporizable antimicrobial agent is present in a concentration of 5 to 85 μg / cm³. 2 A system having a surface area concentration.

13. It's a kit, An orthopedic implant body comprising at least one orthopedic implant body defining an outer implant surface, further defining one or more openings extending from the outer implant surface through the orthopedic implant body and configured to receive a bone fixation device, A plurality of bone fasteners configured to be disposed within at least one opening of the orthopedic implant body for fixing the orthopedic implant body to bone, wherein each of the plurality of bone fasteners comprises a plurality of bone fasteners that each define an outer fastener surface, At least one or more of the openings, and one or both of the corresponding outer fastener surfaces, comprising a biodegradable polymer thin film, The biodegradable polymer thin film contains a vaporizable antimicrobial agent, The biodegradable polymer thin film has a range of 50 to 250 μg / cm 2 areal coating weight The vaporizable antimicrobial agent is present in a concentration of 5 to 85 μg / cm³. 2 A kit having a surface area concentration.

14. A method for reducing the loss of release torque resulting from antimicrobial treatment of an orthopedic implant system, wherein the orthopedic implant system is An orthopedic implant body defining the outer surface of an implant, further defining one or more openings extending from the outer surface of the implant through the orthopedic implant body and configured to receive a bone fastening device, A bone fastener configured to be disposed within one or more openings for fixing the orthopedic implant body to bone, comprising a bone fastener defining the outer surface of the fastener, The method described above is Applying a biodegradable polymer thin film to one or both of the one or more openings and the corresponding outer fastener surfaces, This includes incorporating a vaporizable antimicrobial agent into the biodegradable polymer thin film, The biodegradable polymer thin film is 50 to 250 μg / cm³ 2 It has a surface area coating weight, The vaporizable antimicrobial agent is present in a concentration of 5 to 85 μg / cm³. 2 A method having a surface area concentration.

Citation Information

Patent Citations

  • Antimicrobial packaged medical device and method of making same

    JP2006501975A

  • A method for coating the metal surface of medical devices with an anti-infective agent.

    JP2012504020A

  • Adjustable bioactive agent dispersion within a polymeric coating

    US20150031772A1